Dating the tombs of the Egyptian Old Kingdom - Swinton, Joyce (Egyptologist) (Archaeopress Egyptology, 2014)
The decorated tombs of the Egyptian Old Kingdom offer detailed knowledge of a society that in all probability was the first nation state in history. Yet scholars continue to find it difficult to access the full potential of this great body of data because so few of the tombs can be dated with sufficient precision to provide a relative chronology for the evidence they offer. The system of dating these monuments presented here builds on the work of previous scholars. In this volume the author explains how the dating method was devised. This required establishing 'life-spans' for 104 criteria, features drawn from tomb iconography.